A kind of crude oil oiling type FDY oil and its preparation method
Patent Information
- Application Number
- CN202610151735.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-02-03
AI Technical Summary
这类抗静电剂通常依赖吸湿或形成弱极性导电通路来消散静电,在低湿度环境下抗静电效果明显下降,环境适应性较差
(1)本申请将碳纳米管引入离子液体中,使碳纳米管作为导电结构增强相分散于离子液体内部,通过其高长径比形成连续或半连续的导电支撑网络,对离子液体的离子传输路径起到稳定和延展作用,从而显著提高抗静电性能的稳定性和持续性;(2)本申请通过先将离子液体-碳纳米管复合抗静电剂引入极性溶剂中,可利用极性溶剂对离子液体的良好相容性以及对碳纳米管的润湿作用,使复合抗静电剂在分子或纳米尺度上形成更加均匀、稳定的分散状态。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of textile auxiliaries technology, and in particular to a crude oil-based FDY oiling agent and its preparation method. Background Technology
[0002] During the spinning, drawing, and subsequent winding processes of fully drawn polyester yarn (FDY), the fiber surface is highly susceptible to the accumulation of static electricity due to high-speed friction and contact separation. This static electricity not only leads to fiber adsorption, yarn bundle disarray, and increased breakage rates, but also causes dust adsorption and equipment contamination, severely impacting the stability of the spinning process and the quality of the finished fiber. Therefore, in FDY production, it is typically necessary to apply a spinning oil with lubricating, bundling, and antistatic functions to the fiber surface.
[0003] Existing FDY oils can be classified into emulsion-type oils and crude oil-based oils according to their application methods. Crude oil-based FDY oils are water-free and offer advantages such as system stability, no need for emulsification, and simplified storage and usage processes, leading to their widespread application in high-speed spinning and continuous production in recent years. However, because crude oil-based FDY oils are non-aqueous systems, achieving their antistatic properties is more difficult, placing higher demands on the selection of antistatic agents and dispersion stability.
[0004] Currently, commonly used antistatic agents in crude oil-based FDY oiling agents mainly include nonionic antistatic agents, quaternary ammonium salt antistatic agents, or other surface-active substances. These antistatic agents typically rely on moisture absorption or the formation of weakly polar conductive pathways to dissipate static electricity. Their antistatic effect decreases significantly in low-humidity environments, resulting in poor environmental adaptability. Furthermore, some antistatic agents have limited compatibility in oily systems, easily precipitating, migrating, or failing over time, making it difficult to meet the requirements for antistatic durability and stability during high-speed spinning. Therefore, there is an urgent need to develop an antistatic technology solution suitable for crude oil-based FDY oiling agents to meet the needs of high-speed spinning and high-quality polyester fiber production. Summary of the Invention
[0005] In view of the above-mentioned shortcomings in the prior art, the purpose of this application is to provide a crude oil-adding FDY agent and its preparation method.
[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, embodiments of this application provide a method for preparing a crude oil-based FDY additive, comprising: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to a polar solvent and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. The S300 includes: S310. Divide the base oil into a first base oil and a second base oil. Add an antistatic agent dispersion and an emulsifier to the first base oil and stir to obtain an antistatic agent emulsion. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the antistatic agent emulsion to the oil phase and disperse it to obtain crude oil-based FDY oiling agent.
[0007] In an optional implementation, S100 includes: S110. Carbon nanotubes are added to an ionic liquid and ultrasonically dispersed to obtain an ionic liquid-carbon nanotube composite antistatic agent.
[0008] In one alternative implementation, the mass ratio of ionic liquid to carbon nanotubes is (5-30):1.
[0009] In one alternative embodiment, the ionic liquid includes at least one or a combination of imidazole ionic liquids, pyridine ionic liquids, and quaternary ammonium ionic liquids; and / or the ultrasonic dispersion treatment temperature is 40-80°C; and / or the ultrasonic dispersion treatment time is 30-120 min.
[0010] In an optional embodiment, the carbon nanotubes are pretreated carbon nanotubes, the pretreatment including: S111. Carbon nanotubes are added to an acid solution and allowed to stand. After the standing process is completed, they are washed and dried. The acid solution includes nitric acid solution or nitric acid-sulfuric acid mixture solution.
[0011] In one optional embodiment, the settling temperature is 40-70°C; and / or the settling time is 2-6 hours; and / or the drying temperature is 60-100°C.
[0012] In an alternative embodiment, the polar solvent includes at least one or a combination of deionized water, methanol, ethanol, butanediol, n-butanol, and isopropanol; and / or the base oil includes at least one or a combination of white oil, mineral oil, polyalphaolefin, diisooctyl adipate, and trimethylolpropane; and / or the functional component includes at least one or a combination of bridging agents and smoothing agents.
[0013] In one alternative embodiment, the mass ratio of emulsifier to ionic liquid-carbon nanotube composite antistatic agent is (1.2-1.5):1; and / or the mass ratio of the first part of base oil to the second part of base oil is 1:(3-10); and / or the amount of ionic liquid-carbon nanotube composite antistatic agent is 0.05-1 wt.% of the total amount of crude oil-based FDY oil; and / or the mass ratio of clustering agent, smoothing agent and ionic liquid-carbon nanotube composite antistatic agent is 1:(0.6-1.6):(0.5-1.4).
[0014] In an optional implementation, S330 includes: S331. Add the oil solution of the antistatic agent to the oil phase, heat to 80-120℃ for the first dispersion treatment for 30-90 min, and then cool to 40-60℃ for the second dispersion treatment for 20-60 min to obtain the intermediate oil agent. S332. Stabilize the intermediate oil agent for 8-24 hours to obtain crude oil-based FDY oil agent.
[0015] Secondly, this application provides a crude oil-adding FDY agent, which is prepared using any of the preparation methods described above.
[0016] The beneficial effects of this application include at least the following: (1) This application introduces carbon nanotubes into ionic liquids, so that carbon nanotubes are dispersed inside the ionic liquid as a conductive structure reinforcement phase. Through their high aspect ratio, they form a continuous or semi-continuous conductive support network, which plays a stabilizing and extending role in the ion transport path of the ionic liquid, thereby significantly improving the stability and sustainability of the antistatic performance; (2) This application introduces the ionic liquid-carbon nanotube composite antistatic agent into a polar solvent first. The good compatibility of the polar solvent with the ionic liquid and the wetting effect on the carbon nanotubes can be used to make the composite antistatic agent form a more uniform and stable dispersion state at the molecular or nanoscale. Detailed Implementation
[0017] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are only for explaining this application, but the implementation of this application is not limited thereto.
[0018] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this application pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; the amounts of experimental reagents used are, unless otherwise specified, the amounts used in conventional experimental operations; and the experimental methods used are, unless otherwise specified, conventional methods.
[0019] Polyester fully drawn yarn is prone to static electricity generation during production due to high-speed friction, leading to problems such as yarn bundle disarray and increased breakage rate, affecting production stability and fiber quality. To address this issue, spinning oils are needed. Oil-based FDY oils are increasingly widely used in high-speed spinning due to their advantages such as being water-free, having a stable system, and being easy to use. However, these oils are non-aqueous systems, posing challenges to achieving antistatic properties: traditional antistatic agents often rely on hygroscopic conductivity, resulting in significantly reduced effectiveness in low-humidity environments and poor environmental adaptability; furthermore, their compatibility with oily systems may be poor, leading to precipitation, migration, or aging issues, making it difficult to meet the requirements of long-lasting and stable antistatic properties in high-speed spinning. This application provides a crude oil-based FDY oiling agent and its preparation method. By using an ionic liquid-carbon nanotube composite antistatic agent and processing the base oil in stages, the antistatic components are first formed into an oil solution and then introduced into an oil phase system containing functional components. After dispersion treatment, a crude oil-based FDY oiling agent is obtained, thereby achieving the stable introduction of antistatic components into the oily system and improving the uniformity and stability of the oiling agent system.
[0020] In a first aspect, embodiments of this application provide a method for preparing a crude oil-based FDY additive, comprising: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to a polar solvent and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. The S300 includes: S310. Divide the base oil into a first base oil and a second base oil. Add an antistatic agent dispersion and an emulsifier to the first base oil and stir to obtain an antistatic agent emulsion. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the antistatic agent emulsion to the oil phase and disperse it to obtain crude oil-based FDY oiling agent.
[0021] Preferably, this application first prepares an ionic liquid-carbon nanotube composite antistatic agent and then adds it to the base oil and functional components, which helps to ensure the uniformity and stability of the final crude oil-based FDY oil agent. Specifically, in step S100, the ionic liquid-carbon nanotube composite antistatic agent is first prepared. Since the ionic liquid itself is rich in freely moving ions, it can provide a conductive path without relying on water molecules, and can achieve stable and efficient antistatic properties under all humidity conditions. Furthermore, the ionic liquid has high thermal and chemical stability, as well as extremely low saturated vapor pressure, and is not easily decomposed or volatilized at high temperatures. It can not only continuously exert its antistatic effect, but also effectively reduce the problem of coking on the hot roller caused by thermal decomposition products, making it an ideal antistatic agent. However, if ionic liquids are used alone as antistatic agents, the antistatic effect still decays over time. Therefore, this application introduces carbon nanotubes (CNTs) into ionic liquids, allowing them to act as a conductive reinforcing phase dispersed within the ionic liquid. Through their high aspect ratio, CNTs form a continuous or semi-continuous conductive support network, stabilizing and extending the ion transport pathways of the ionic liquid, thereby significantly improving the stability and sustainability of the antistatic performance. Furthermore, the composite system formed by the ionic liquid and carbon nanotubes also helps improve the structural integrity of the antistatic agent during subsequent dispersion, reducing the risk of agglomeration associated with direct addition of carbon nanotubes to oily systems.
[0022] Furthermore, S100 includes: S110. Carbon nanotubes are added to an ionic liquid and ultrasonically dispersed to obtain an ionic liquid-carbon nanotube composite antistatic agent.
[0023] Preferably, the ionic liquid is composed of organic cations and inorganic or organic anions, possessing high polarity and a tunable ionic structure. Its ion pairs can form a stable adsorption layer on the carbon nanotube surface through electrostatic interactions, π-π interactions, and van der Waals forces, thereby constructing a continuous ionicly conductive environment on the outer surface of the carbon nanotubes. This physical adsorption and interfacial interaction achieves stable anchoring of the ionic liquid on the carbon nanotube surface without the need for covalent bonding, while avoiding structural damage or decreased conductivity of the carbon nanotubes that may be caused by chemical modification. The ionic liquid includes at least one or a combination of imidazole, pyridine, and quaternary ammonium ionic liquids. These ionic liquids possess high ion mobility, good thermal stability, and strong interaction capabilities with carbon nanomaterials, enabling them to form a stable ionicly conductive environment in the composite system. Carbon nanotubes themselves have a high aspect ratio and are prone to forming spatial network structures. During ultrasonic dispersion, the ultrasonic cavitation effect effectively breaks down carbon nanotube aggregates, allowing them to exist in a dispersed state in the ionic liquid and gradually form an interconnected supporting network structure within the system. This network structure not only provides a continuous and stable conductive channel for ion migration in the ionic liquid, but also macroscopically inhibits the re-agglomeration of carbon nanotubes. This allows the resulting composite antistatic agent to maintain good dispersion stability and antistatic properties even without additional stabilizers or complex treatments. Ultrasonic dispersion at 40-80℃ for 30-120 min effectively dissociates carbon nanotube aggregates through cavitation without damaging the ionic liquid structure, improving its dispersion uniformity. When the amount of ionic liquid is too small, it is difficult to provide sufficient continuous medium for the carbon nanotubes, easily leading to agglomeration and weakening the conductive continuity of the composite antistatic agent. Conversely, excessive ionic liquid will reduce the effective support and reinforcement effect of carbon nanotubes in the composite system, hindering the formation of a stable composite conductive network. Therefore, a mass ratio of ionic liquid to carbon nanotubes of (5-30):1 can achieve a balance between ionic conductivity and structural reinforcement while ensuring sufficient dispersion of carbon nanotubes.
[0024] Furthermore, the carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. Carbon nanotubes are added to an acid solution and allowed to stand. After the standing process is completed, they are washed and dried. The acid solution includes nitric acid solution or nitric acid-sulfuric acid mixture solution.
[0025] Preferably, acid treatment can introduce oxygen-containing functional groups such as carboxyl and hydroxyl groups onto the surface of carbon nanotubes, improving their surface polarity and wettability, thereby enhancing their interaction with ionic liquids and further improving dispersion stability. The standing treatment temperature is 40-70℃ for 2-6 hours, which helps to ensure the surface functionalization effect while avoiding excessive oxidation that could damage the carbon nanotube structure. The washing treatment uses deionized water to remove residual acid, and this washing treatment is repeated at least three times. The drying treatment temperature is 60-100℃, which effectively removes residual solvent and acid while avoiding functional group removal or structural degradation caused by high temperatures.
[0026] Preferably, in step S200, the ionic liquid-carbon nanotube composite antistatic agent is mixed with a polar solvent. By introducing the polar solvent as an intermediate transition phase, the ionic liquid-carbon nanotube composite antistatic agent is initially dispersed and its wetting is controlled. Since ionic liquids are inherently highly polar, and carbon nanotubes exhibit certain π-electron structures and surface energy differences, directly introducing the composite antistatic agent into an oily system can easily lead to dispersion barriers or localized aggregation at the interface. By first introducing it into a polar solvent, the good compatibility of the polar solvent with the ionic liquid and its wetting effect on the carbon nanotubes can be utilized, allowing the composite antistatic agent to form a more uniform and stable dispersion at the molecular or nanoscale. The polar solvent includes at least one or a combination of deionized water, methanol, ethanol, butanediol, n-butanol, and isopropanol. This step effectively reduces the interfacial tension differences during subsequent emulsification and oil phase integration processes, providing a good structural basis for the smooth entry of the antistatic agent into the oily system.
[0027] Preferably, in step S300, the antistatic agent dispersion is introduced into the base oil and functional components, and its stable integration in the oily system is achieved through dispersion treatment. By dispersing the ionic liquid-carbon nanotube composite antistatic agent with a polar solvent before introduction and using an emulsifier for interface control during integration into the oil phase, direct and disordered contact between the antistatic agent and functional components in the initial stage can be effectively avoided, thereby reducing the impact of uncontrollable interactions caused by compatibility differences or sudden changes in local concentration on the stability of the system. At the same time, through stepwise introduction and dispersion treatment, the ionic liquid-carbon nanotube composite antistatic agent can exist stably in the oily continuous phase in a refined and uniform state, which is conducive to the consistent performance of antistatic function in the entire oil formulation system, thereby obtaining a crude oil-based FDY oil formulation with uniform composition, stable structure, and controllable performance. The base oil includes at least one or a combination of white oil, mineral oil, polyalphaolefin, diisooctyl adipate, and trimethylolpropane ester. White oil and mineral oil, as non-polar base oils, possess good thermal stability and chemical inertness, and can serve as the continuous phase in the oil system, meeting the basic requirements for high-temperature resistant, low-volatility, and non-swelling fiber materials during FDY spinning. Polyalphaolefin has a high viscosity index and excellent shear stability, which is beneficial for maintaining oil film stability under high-speed spinning conditions. Diisooctyl adipate and trimethylolpropane ester, as ester base oils with certain polarity, can improve the oil phase system's performance in ionic liquid-carbon nanotube composites. The compatibility of antistatic agents and polar solvents reduces the risk of phase separation, thereby improving the stability and durability of antistatic function in oily systems. Functional components include at least one or a combination of bundle agents and smoothing agents. Bundle agents are used to stabilize the fiber bundle structure and suppress fraying, while smoothing agents are used to reduce the coefficient of friction between fibers and guide components and between fibers. The above functional components work synergistically with the base oil, so that the resulting oil can meet the requirements for operational stability and processing adaptability in crude oil-based FDY spinning while ensuring antistatic performance. In addition, those skilled in the art can add antioxidants, defoamers, preservatives, etc. as needed.
[0028] Preferably, in step S310, the antistatic agent dispersion and emulsifier are added to the first portion of base oil for thorough dispersion. The introduction of the emulsifier creates a stable interfacial structure between the polar solvent phase, the ionic liquid-carbon nanotube composite antistatic agent, and the base oil, thereby effectively encapsulating and stably dispersing the originally highly polar antistatic agent within the oil phase. By first forming an antistatic agent emulsion, the risk of interfacial conflict and local concentration abrupt changes when the antistatic agent is directly incorporated into the main oil phase can be significantly reduced. This avoids aggregation, precipitation, or stratification of the ionic liquid or carbon nanotubes due to insufficient compatibility, ensuring the stability of the overall oil system. The mass ratio of the first and second base oils is 1:(3-10) to provide sufficient oil phase volume during the antistatic agent emulsion formation stage to buffer the incorporation of the polar dispersed phase, while ensuring that the functional components are fully and uniformly dispersed in the main oil phase. When the proportion of the first base oil is too low, the antistatic agent dispersion is prone to local high concentrations during emulsification, increasing the risk of phase separation. When the proportion of the first base oil is too high, it will weaken the effective concentration of the functional components in the main oil phase, which is not conducive to the performance of the bundling and smoothing functions. If the amount of ionic liquid-carbon nanotube composite antistatic agent is too low, it is difficult to form a continuous and effective conductive path on the fiber surface. If the amount is too high, it will significantly increase the polarity of the system, destroy the continuous structure of the oil phase, and thus affect the lubrication stability and the reliability of the oil under high-speed spinning conditions. Therefore, the amount of ionic liquid-carbon nanotube composite antistatic agent should be 0.05-1 wt.% of the total amount of crude oil-based FDY oil. Because ionic liquid-carbon nanotube composite antistatic agents possess both strong polarity and high specific surface area, their requirements for interfacial stability are significantly higher than those for conventional antistatic agents. When the amount of emulsifier is insufficient, it is difficult to provide adequate interfacial coverage for the polar dispersed phase formed by the ionic liquid and carbon nanotubes, which can easily lead to the aggregation or stratification of the antistatic agent in the oil phase, thus affecting the long-term stability of antistatic performance. On the other hand, when the amount of emulsifier is too high, it can cause an increase in system viscosity, a decrease in lubrication performance, and even adverse effects on the clustering and smoothing functions. Therefore, the mass ratio of emulsifier to ionic liquid-carbon nanotube composite antistatic agent is (1.2-1.5):1, which can ensure dispersion stability while taking into account the fluidity and processing adaptability of the oil.
[0029] Further, in step S320, the functional components are added to the second part of the base oil. This step allows the functional components to be fully mixed with the base oil under conditions unaffected by antistatic agents and polar solvents, forming a homogeneous and stable functional oil phase. This step helps to avoid complex or uncontrollable interactions between the functional components and the ionic liquid-carbon nanotube composite antistatic agent in the initial stage, thereby reducing the risk of interference with the antistatic function or degradation of other oil agent functions, ensuring the integrity of the oil agent's main structure and the synergistic and stable performance of its functions. The mass ratio of the bundle agent, smoothing agent, and ionic liquid-carbon nanotube composite antistatic agent is 1:(0.6-1.6):(0.5-1.4), which enables the antistatic function to work synergistically with the bundle and smoothing functions while ensuring the stability of the filament bundle and low friction characteristics.
[0030] Furthermore, in step S330, the antistatic agent emulsion is added to the oil phase for dispersion treatment. Since the antistatic agent is introduced into the system in an emulsified and pre-dispersed state, it is more conducive to its uniform diffusion in the continuous medium of the oil phase compared to directly adding high-concentration antistatic agents or solid components. This promotes the formation of a stable and uniform distribution of the ionic liquid-carbon nanotube composite antistatic agent in the oil phase, ultimately obtaining a crude oil-based FDY oil agent with a uniform appearance, low stratification, stable antistatic performance, and synergistic effect of various functional components.
[0031] Preferably, S330 includes: S331. Add the oil solution of the antistatic agent to the oil phase, heat to 80-120℃ for the first dispersion treatment for 30-90 min, and then cool to 40-60℃ for the second dispersion treatment for 20-60 min to obtain the intermediate oil agent. S332. Stabilize the intermediate oil agent for 8-24 hours to obtain crude oil-based FDY oil agent.
[0032] Preferably, in step S331, after adding the antistatic agent oil solution to the oil phase, the system is first heated to 80-120℃ and subjected to a first dispersion treatment for 30-90 minutes. This helps reduce the viscosity of the base oil and ester components, improves the system's fluidity, and thus enhances shear and diffusion efficiency. This allows the ionic liquid-carbon nanotube composite antistatic agent to quickly overcome the interfacial resistance of the oil phase and achieve rapid and uniform distribution at the macroscopic level. Simultaneously, at higher temperatures, emulsifier molecules and polar components have higher migration capabilities, accelerating their rearrangement and interfacial coverage on the surface of the antistatic agent dispersed phase, laying the foundation for subsequent structural stability. Subsequently, the system is cooled to 40-60℃ and subjected to a second dispersion treatment for 20-60 minutes, allowing the system to complete the refinement and solidification of the interfacial structure under conditions close to the actual operating temperature. Within this temperature range, the oil phase viscosity is moderate, which is conducive to the formation of stable, fine, and uniformly distributed dispersion units of the ionic liquid-carbon nanotube composite antistatic agent in the continuous oil phase medium. Simultaneously, it suppresses the migration or re-aggregation of polar components that may occur under high-temperature conditions, thereby improving the long-term stability of the dispersion structure. By leveraging the synergistic effect of high temperature promoting diffusion and low temperature promoting structural shaping, the risk of insufficient dispersion or subsequent stratification caused by dispersion in a single temperature zone can be effectively avoided.
[0033] In step S332, the obtained intermediate oil is subjected to a stabilization treatment for 8-24 hours. This stabilization treatment involves standing at room temperature, allowing the system to undergo further spontaneous rearrangement and stress release of its internal structure without external shear. This facilitates the emulsifier reaching a thermodynamically stable state at the interface and promotes a more balanced distribution of the ionic liquid-carbon nanotube composite antistatic agent in the oil phase. This stabilization step significantly reduces the risk of stratification, sedimentation, or performance fluctuations during storage and use, resulting in an oil product with a uniform appearance, stable structure, and suitable for long-term use in crude oil-based FDY processes.
[0034] Secondly, this application provides a crude oil-adding FDY agent, prepared using any of the preparation methods described above. Therefore, it possesses all the beneficial effects of the preparation methods for crude oil-adding FDY agents, which will not be elaborated further here.
[0035] Example 1 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to deionized water and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to an imidazole ionic liquid at a mass ratio of 1:5 and ultrasonically dispersed at 40°C for 30 min to obtain an ionic liquid-carbon nanotube composite antistatic agent. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:3. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.2:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The base oil is mineral oil, and the functional components are a binder and a smoother. The mass ratio of the binder, smoother and ionic liquid-carbon nanotube composite antistatic agent is 1:0.6:0.5. The amount of ionic liquid-carbon nanotube composite antistatic agent is 0.05 wt.% of the total mass of crude oil-based FDY oil.
[0036] Example 2 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to ethanol and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to pyridine-based ionic liquid at a mass ratio of 1:30 and ultrasonically dispersed at 80°C for 120 min to obtain ionic liquid-carbon nanotube composite antistatic agent. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:10. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.5:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The base oil is white oil, and the functional components include a clustering agent and a smoothing agent. The mass ratio of the clustering agent, the smoothing agent and the ionic liquid-carbon nanotube composite antistatic agent is 1:1.6:1.4. The amount of the ionic liquid-carbon nanotube composite antistatic agent is 0.05 wt.% of the total mass of the crude oil-based FDY oiling agent.
[0037] Example 3 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to methanol and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to a quaternary ammonium ionic liquid at a mass ratio of 1:15 and ultrasonically dispersed at 60°C for 100 min to obtain an ionic liquid-carbon nanotube composite antistatic agent. The carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. Carbon nanotubes are added to nitric acid solution and allowed to stand at 40°C for 2 hours. After standing, they are washed and dried at 60°C. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:5. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.3:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The base oil is polyalphaolefin, and the functional components include a slub and a lubricant. The mass ratio of the slub, lubricant and ionic liquid-carbon nanotube composite antistatic agent is 1:1:1. The amount of ionic liquid-carbon nanotube composite antistatic agent is 0.5 wt.% of the total mass of crude oil-based FDY oil.
[0038] Example 4 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to methanol and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to a quaternary ammonium ionic liquid at a mass ratio of 1:15 and ultrasonically dispersed at 60°C for 100 min to obtain an ionic liquid-carbon nanotube composite antistatic agent. The carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. Carbon nanotubes are added to nitric acid solution and left to stand at 70°C for 6 hours. After standing, they are washed and dried at 100°C. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:5. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.3:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The base oils are diisooctyl adipate and trimethylolpropane ester. The functional components include a slub and a lubricant. The mass ratio of the slub, lubricant and ionic liquid-carbon nanotube composite antistatic agent is 1:1:1. The amount of ionic liquid-carbon nanotube composite antistatic agent is 0.5 wt.% of the total mass of crude oil-based FDY oil.
[0039] Example 5 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to methanol and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to a quaternary ammonium ionic liquid at a mass ratio of 1:20 and ultrasonically dispersed at 60°C for 100 min to obtain an ionic liquid-carbon nanotube composite antistatic agent. The carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. Carbon nanotubes are added to nitric acid solution and left to stand at 60°C for 4 hours. After standing, they are washed and dried at 80°C. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:5. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.3:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The S330 includes: S331. Add the oil solution of the antistatic agent to the oil phase, heat to 80°C for the first dispersion treatment for 30 min, and then cool to 40°C for the second dispersion treatment for 20 min to obtain the intermediate oil agent. S332. Stabilize the intermediate oil agent for 8 hours to obtain crude oil-based FDY oil agent. The base oils are mineral oil and white oil. The functional components include a binder and a smoother. The mass ratio of the binder, smoother and ionic liquid-carbon nanotube composite antistatic agent is 1:1:1. The amount of ionic liquid-carbon nanotube composite antistatic agent is 0.5 wt.% of the total mass of crude oil-based FDY oil.
[0040] Example 6 This embodiment provides a method for preparing a crude oil-based FDY additive, comprising the following steps: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. Add the ionic liquid-carbon nanotube composite antistatic agent to methanol and mix to obtain an antistatic agent dispersion. S300: Add the antistatic agent dispersion to the base oil and functional components, and after dispersion treatment, obtain the crude oil-based FDY oiling agent. S100 includes: S110. Carbon nanotubes are added to a quaternary ammonium ionic liquid at a mass ratio of 1:20 and ultrasonically dispersed at 60°C for 100 min to obtain an ionic liquid-carbon nanotube composite antistatic agent. The carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. Carbon nanotubes are added to nitric acid solution and left to stand at 60°C for 4 hours. After standing, they are washed and dried at 80°C. The S300 includes: S310. The base oil is divided into a first base oil and a second base oil, with a mass ratio of 1:5. An antistatic agent dispersion and an emulsifier are added to the first base oil, with a mass ratio of 1.3:1 between the emulsifier and the ionic liquid-carbon nanotube composite antistatic agent. After stirring, an antistatic agent emulsion is obtained. S320. Add the functional components to the second part of the base oil and stir to obtain the oil phase; S330. Add the oil solution of the antistatic agent to the oil phase and disperse it to obtain the crude oil-coated FDY oil agent. The S330 includes: S331. Add the oil solution of the antistatic agent to the oil phase, heat to 120°C for the first dispersion treatment for 90 min, and then cool to 60°C for the second dispersion treatment for 60 min to obtain the intermediate oil agent. S332. Stabilize the intermediate oil agent for 24 hours to obtain crude oil-based FDY oil agent. The base oils are mineral oil and white oil. The functional components include a binder and a smoother. The mass ratio of the binder, smoother and ionic liquid-carbon nanotube composite antistatic agent is 1:1:1. The amount of ionic liquid-carbon nanotube composite antistatic agent is 0.5 wt.% of the total mass of crude oil-based FDY oil.
[0041] Comparative Example 1 This embodiment provides a method for preparing a crude oil-based FDY oiling agent. The difference from Embodiment 1 is that a quaternary ammonium salt antistatic agent is used, i.e., steps S100 and S110 are omitted.
[0042] Comparative Example 2 This embodiment provides a method for preparing crude oil-based FDY oiling agent. The difference from Embodiment 1 is that step S200 is omitted, that is, in step S310, an ionic liquid-carbon nanotube composite antistatic agent is directly added.
[0043] Comparative Example 3 This embodiment provides a method for preparing crude oil-based FDY oil additive. The difference from Embodiment 1 is that the base oil is not divided into two parts. All the base oil is added in step S310 and step S320 is omitted. In step S330, the functional components are directly added to the antistatic agent emulsion in step S310.
[0044] Comparative Example 4 This embodiment provides a method for preparing crude oil-based FDY oil agent. The difference from Embodiment 1 is that the base oil is not divided into two parts. All the base oil is added in step S320 and step S310 is omitted. In step S330, the antistatic agent dispersion is directly added to the oil phase.
[0045] Comparative Example 5 This embodiment provides a crude oil-based FDY additive, which differs from Embodiment 6 in that it does not undergo stabilization treatment, i.e., step S332 is omitted.
[0046] This application has undergone multiple experiments, and some of the test results are presented here for reference to further describe the invention in detail. The following is a detailed description in conjunction with specific embodiments.
[0047] Performance testing Electrostatic voltage test on fiber surface: According to GB / T 12703.1, under the conditions of 23℃, 30% relative humidity and FDY fiber linear speed of 6000 m / min, the crude oil-oiling type FDY oiling agent prepared in Examples 1-6 and Comparative Examples 1-5 was used for oiling. The electrostatic voltage on the fiber surface was measured immediately after oiling. The test results are shown in Table 1.
[0048] Table 1 As shown in Table 1, Examples 1-6, which used ionic liquid-carbon nanotube composite antistatic agents and underwent polar dispersion and stepwise integration treatment, exhibited significantly lower electrostatic voltages on the fiber surfaces compared to Comparative Examples 1-5, especially maintaining stable antistatic effects under low humidity conditions. In Comparative Example 1, which used only conventional quaternary ammonium salt antistatic agents, the electrostatic voltage increased significantly, indicating that the composite antistatic system has a clear advantage in terms of antistatic persistence.
[0049] Stability test: 100 mL of crude oil-based FDY oil samples from Examples 1-6 and Comparative Examples 1-5 were placed in a 50℃ constant temperature oven and left to stand for 7 days. The results are shown in Table 2.
[0050] Table 2 As shown in Table 2, no stratification or sedimentation occurred in Examples 1-6. Comparative Example 1 used a test-type antistatic agent. Due to the lack of polar dispersion, segmented integration, or stabilization treatment steps, the oil systems of Comparative Examples 1-5 showed varying degrees of stratification or sedimentation during storage. However, the samples in the examples all maintained a uniform appearance, indicating that the step-by-step integration and stabilization process of this application significantly improved the structural stability of the oil system.
[0051] Friction coefficient test: The friction coefficient μ of the yarns after being oiled with crude oil-based FDY oiling agents of Examples 1-6 and Comparative Examples 1-5 was tested using a yarn friction coefficient tester. The test results are shown in Table 3.
[0052] Table 3 As can be seen from Table 3, the yarns using the crude oil-oiled FDY lubricant of Examples 1-6 significantly reduced the static electricity level while maintaining a low coefficient of friction. This indicates that the ionic liquid-carbon nanotube composite antistatic system did not damage the lubrication function of the lubricant. In contrast, the yarns using the crude oil-oiled FDY lubricant of Comparative Examples 1-5 showed significantly deteriorated friction performance.
[0053] High-speed spinning breakage rate test: FDY was run continuously for 8 hours, the number of breakages was counted, and the breakage rate was calculated. The results are shown in Table 4.
[0054] Table 4 As shown in Table 4, the samples using crude oil-based FDY oils from Examples 1-6 showed a significant reduction in breakage rate under high-speed spinning conditions, indicating that the oil system has a synergistic effect in terms of antistatic properties, lubrication, and structural stability. However, the samples using crude oil-based FDY oils from Comparative Examples 1-5 had insufficient antistatic properties or poor system stability, resulting in static electricity accumulation and uneven friction during spinning, leading to a significant increase in breakage rate.
[0055] Coking performance test: 1.0 ml of crude oil-based FDY oil sample from Examples 1-6 and Comparative Examples 1-5 was dropped onto a steel sheet. The steel sheet was placed in an oven at 220°C for 3 min and then cooled to 25°C. The coking performance of the sample was observed. The test results are shown in Table 5.
[0056] Table 5 As shown in Table 5, the crude oil-coated FDY agents in Examples 1-6 showed almost no coking, indicating that the crude oil-coated FDY agents of this application have excellent anti-coking performance. In contrast, the crude oil-coated FDY agents in Comparative Examples 1-5 all showed obvious brown deposits, indicating that they are more prone to producing thermal decomposition coke and adhering to the metal surface under high temperature conditions. Comparative Example 1, which used a conventional quaternary ammonium salt antistatic agent, showed the most severe coking, indicating that it is more prone to deposition under high temperature thermal shock conditions. Comparative Example 2 lacked a polar medium pre-dispersion step, and the composite antistatic agent was prone to local enrichment or agglomeration in the oil phase, resulting in still severe coking, indicating that the S200 step has a significant effect on reducing coking deposition caused by local high concentration. Comparative Examples 3 and 4 did not introduce the antistatic emulsion and functional oil phase in stages, resulting in disordered contact during the initial mixing stage, leading to reduced thermal stability and increased coking tendency of the system. Compared to Example 5, which did not undergo stabilization treatment, the coking situation was significantly higher than in the corresponding embodiment. This indicates that stabilization treatment helps the system interface structure and component distribution reach a more stable state, thereby reducing the risk of structural rearrangement and coking under high-temperature conditions. The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application, and should all be included within the protection scope of this application.
Claims
1. A method for preparing a crude oil-based FDY oiling agent, characterized in that, include: S100, Preparation of ionic liquid-carbon nanotube composite antistatic agent; S200. The ionic liquid-carbon nanotube composite antistatic agent is added to a polar solvent and mixed to obtain an antistatic agent dispersion. S300. The antistatic agent dispersion is added to the base oil and functional components, and after dispersion treatment, crude oil-based FDY oil agent is obtained. S300 includes: S310. Divide the base oil into a first part of the base oil and a second part of the base oil, add the antistatic agent dispersion and emulsifier to the first part of the base oil, and stir to obtain an antistatic agent emulsion. S320. The functional component is added to the second part of the base oil, and the mixture is stirred to obtain an oil phase. S330. The antistatic agent emulsion is added to the oil phase and the dispersion treatment is performed to obtain the crude oil-coated FDY oil agent. The S330 includes: S331. Add the oil solution of the antistatic agent to the oil phase, heat to 80-120℃ for a first dispersion treatment for 30-90 min, and then cool to 40-60℃ for a second dispersion treatment for 20-60 min to obtain the intermediate oil agent. S332. Stabilize the intermediate oil agent for 8-24 hours to obtain the crude oil-based FDY oil agent. The mass ratio of the ionic liquid to the carbon nanotubes is (5-30):1; The base oil includes at least one or a combination of white oil, mineral oil, polyalphaolefin, diisooctyl adipate and trimethylolpropane ester; The functional components include at least one or a combination of a slub and a smoothing agent; The mass ratio of the emulsifier to the ionic liquid-carbon nanotube composite antistatic agent is (1.2-1.5):1; The mass ratio of the first portion of the base oil to the second portion of the base oil is 1:(3-10); The amount of the ionic liquid-carbon nanotube composite antistatic agent is 0.05-1 wt. of the total mass of the crude oil-based FDY oiling agent.
2. The preparation method according to claim 1, characterized in that, S100 includes: S110. Carbon nanotubes are added to an ionic liquid and ultrasonically dispersed to obtain the ionic liquid-carbon nanotube composite antistatic agent.
3. The preparation method according to claim 2, characterized in that, The ionic liquid includes at least one or a combination of imidazole ionic liquids, pyridine ionic liquids, and quaternary ammonium ionic liquids; and / or The ultrasonic dispersion treatment is performed at a temperature of 40-80℃; and / or The ultrasonic dispersion treatment time is 30-120 min.
4. The preparation method according to claim 2, characterized in that, The carbon nanotubes are pretreated carbon nanotubes, and the pretreatment includes: S111. The carbon nanotubes are added to an acid solution and allowed to stand for a period of time. After the standing process is completed, the carbon nanotubes are washed and dried. The acid solution includes a nitric acid solution or a nitric acid-sulfuric acid mixture.
5. The preparation method according to claim 4, characterized in that, The temperature for the settling process is 40-70℃; and / or The settling time is 2-6 hours; and / or The drying process is carried out at a temperature of 60-100℃.
6. The preparation method according to claim 1, characterized in that, The polar solvent includes at least one or a combination of deionized water, methanol, ethanol, butanediol, n-butanol and isopropanol.
7. The preparation method according to claim 1, characterized in that, The mass ratio of the slubbing agent, the smoothing agent, and the ionic liquid-carbon nanotube composite antistatic agent is 1:(0.6-1.6):(0.5-1.4).
8. A crude oil-adding FDY agent, characterized in that, The crude oil-based FDY oil additive is prepared using the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Antistatic agent for polyurethane, and polyurethane composite material and preparation method thereof
CN111187447A
FDY (fully drawn yarn) oiling agent capable of being directly oiled from crude oil, preparation method and spinning device
CN120556174A